Characteristics of patients with viral infections of the lower respiratory tract: A retrospective study. Issue 38 (23rd September 2022) - Nabeya, Daijiro; Kinjo, Takeshi; Ueno, Shiho; Setoguchi, Michika; Nishiyama, Naoya; Kami, Wakaki; Arakaki, Wakako; Haranaga, Shusaku; Fujita, Jiro
Abstract : While the impact of respiratory virus infections has been well researched in some respiratory diseases, no clinical studies have discussed the subject of who would be more likely to develop respiratory virus infections among patients with various respiratory illnesses who come from different backgrounds. This study aimed to identify respiratory diseases that are frequently associated with respiratory virus infections along with the characteristics of patients who develop such infections in clinical settings. Tested specimens were obtained from the lower respiratory tract by bronchoscopy to provide more accurate data. Data of bronchoscopies at Ryukyu University Hospital between August 2012 and September 2016 were reviewed, and patients who underwent multiplex polymerase chain reaction (PCR) tests for detecting respiratory viruses in bronchoscopy specimens were retrospectively recruited for descriptive statistics. Differences among patients' primary pulmonary diseases and backgrounds were compared between the PCR-positive and -negative patients, and multivariate statistical analysis was performed to analyze factors associated with a positive PCR test result. Overall, 756 bronchoscopies were performed during the study period and PCR tests were performed for 177 patients. Of them, 27 tested positive for respiratory viruses, mainly parainfluenza virus and rhinovirus, and out of those, 7 were hospitalized for >1 month. Overall, all patients did not experience typical upper respiratory infection symptoms. In positive patients, 13 and 7 had diagnoses of interstitial lung disease and bacterial pneumonia, respectively. The diagnoses of 3 bacterial pneumonia cases were changed to viral pneumonia after receiving their PCR-positive tests. Respiratory virus infections were confirmed in 14 patients on immunosuppressant therapy and 4 on maintenance dialysis. Multivariate analysis revealed that immunosuppressant therapy and maintenance dialysis were independently associated with respiratory virus infections. Viruses were commonly detected in patients with interstitial lung diseases and bacterial pneumonia, while few patients were diagnosed with pure viral pneumonia. These illnesses were considered to be induced by respiratory infections. Immunosuppressant therapy and maintenance dialysis were associated with respiratory virus infections. Multiplex PCR testing is an essential diagnostic tool for respiratory virus infections in immunocompromised patients.